Identifying competitive tin- or metal-free catalyst combinations to tailor polyurethane prepolymer and network properties. Issue 36 (2nd September 2020) - Arnould, Priscilla; Bosco, Lionel; Sanz, Federico; Simon, Frédéric N.; Fouquay, Stéphane; Michaud, Guillaume; Raynaud, Jean; Monteil, Vincent
Abstract : Polyurethane-based mastics, industrially obtained via a prepolymerization/crosslinking process, benefit from catalyst selection at both stages. Abstract : The influences of selected catalysts on the structures and properties of polyurethane prepolymers and networks are investigated to adjust the catalyst/structure/property relationship to a targeted application. This study highlights the necessity of catalysis for polyurethane synthesis, both at the prepolymer and at the crosslinking stages, and emphasizes on the catalyst-dependency of each stage. We also suggest some tin-free and overall metal-free alternatives to ubiquitous tin-based catalysts with metals such as Bi, Ti, Zn and organic catalysts such as DABCO, DMDEE. In polyurethane formulations without fillers, the strong interwoven urethane- and urea-devired H-bonding network is mainly responsible for the mechanical properties of the material and tends to overshadow the catalyst effects. Nonetheless, in the presence of fillers such as those used in industrial polyurethane formulations, tensile tests evidenced that mechanical properties are affected and can be tailored by the choice of catalyst.